TOOTH EXTRACTION FOR HIV PATIENTS: A COMMUNITY SERVICE - Sumarta, Ni Putu Mira; Rizqiawan, Andra; Anugraha, Ganendra; Barus, Liska; Dewantara, Danang; Kusumawardhini, Pralita; Musta'inah, Ita (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2024)
Introduction: Patients with HIV often encounter significant oral health difficulties that can impact their overall well-being. Tooth extraction stands as a pivotal intervention to address these issues. A community service was conducted to give free tooth extraction to HIV patients and to educate patients on how such procedures can enhance their oral health by eliminating dental focal infections. Furthermore, it includes a survey component to assess patient satisfaction levels. Methods: A community service was conducted from June-August 2023 by Department of Oral and Maxillofacial Surgery at the Faculty of Dental Medicine, Universitas Airlangga, in collaboration with Yayasan Mahameru-Surabaya, Universitas Airlangga Dental Hospital. The objective was to provide oral health education, screening and tooth extraction to HIV patients, member of Yayasan Mahameru Surabaya. Tooth extractions was done by staffs and residents, telemedicine follow-up was conducted seven days post-extraction. A satisfaction survey utilizing semi-quantitative questionnaires was done to evaluate the patients' experiences with the service. Results: Forty-five HIV patients screened and 16 patients receiving tooth extraction.  The results of the survey showed that patients were satisfied with this community service activities. Questionaire  result: ease of  access to health provider (50%), ease in obtaining service (68%) patient safety during treatment (81,25%) and sufficient facility (75%). Conclusion: Community service in providing free tooth extraction for HIV patients is an effective method to ease patients accessing dental services and patients showed good satisfaction with dental services.